Short Notes on a Model of the Trade Cycle - Marrama, Vittorio (Review of Economic Studies, 1946)
Journal Article Short Notes on a Model of the Trade Cycle Get access Vittorio Marrama Vittorio Marrama Rome Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 1, 1946, Pages 34–40, https://doi.org/10.2307/2295755 Published: 01 April 1946